2002
DOI: 10.1557/proc-749-w13.5
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Ordering in Self-assembled Epitaxial II-VI and IV-VI Compound Semiconductor Quantum Dot Systems

Abstract: Transmission electron microcopy (TEM) in both the parallel illumination and scanning probe mode revealed atomically ordered entities within a 5 to 250 nm range in a IV-VI and a II-VI compound semiconductor quantum dot (QD) system. While the II-VI system was a nominal [001] CdSe/(Mn 0.1 Zn 0.9 )Se multilayer structure with the QDs embedded, the IV-VI system nominally consisted of [111] PbSe islands. The comparison of photoluminescence (PL) spectra from the CdSe/(Mn 0.1 Zn 0.9 )Se structure with those of a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Preliminary TEM results showed that there is also atomic ordering somewhere in the structure of free-standing three-dimensional (3D) nominal PbSe nano-islands on nominal PbSe wetting layers that were grown in the Stranski-Krastanow mode by means of MBE on PbTe/BaF 2 pseudo-substrates [12].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary TEM results showed that there is also atomic ordering somewhere in the structure of free-standing three-dimensional (3D) nominal PbSe nano-islands on nominal PbSe wetting layers that were grown in the Stranski-Krastanow mode by means of MBE on PbTe/BaF 2 pseudo-substrates [12].…”
Section: Introductionmentioning
confidence: 99%